Multiscale Model for Electrokinetic Transport in Networks of Pores, Part II: Computational Algorithms and Applications - Alizadeh, Shima; Mani, Ali (Langmuir, 2017)
The first part of this two-article series presented a robust mathematical model for the fast and accurate prediction of electrokinetic phenomena in porous networks with complex topologies. In the second part of this series, we first present a numerical algorithm that can efficiently solve the model equations. We then demonstrate that the resulting framework is capable of capturing a wide range of transport phenomena in microstructures by considering a hierarchy of canonical problems with increasing complexity. The developed framework is validated against direct numerical simulations of deionization shocks in micropore-membrane junctions and concentration polarization in micro- and nanochannel systems. We demonstrate that for thin pores subject to concentration gradients our model consistently captures correct induced osmotic pressure, which is a macroscopic phenomena originally derived from thermodynamic principles but here is naturally predicted through microscopic electrostatic interactions. Moreover, we show that the developed model captures current rectification phenomena in a conical nanopore subject to an axial external electric field. Finally, we provide discussions on examples involving stationary and moving deionization shocks in micropore nanopore T-junctions as well as induced-flow loops when pores of varying sizes are connected in parallel.